Процеси та організація комутації вольтододавчих трансформаторів - Халіков, В.А. (Технічна електродинаміка, 2011)
Transient processes appearing over core saturation on switching of the primary winding of a buck–boost transformer are considered. Visual modeling of transient processes is done wiht MATLAB and techniques for minimization or elimination of transients are suggested.